The reproach of hunger: food, justice, and money in the twenty-first century - Rieff, David (New York, 2015)
"In a groundbreaking book, based on six years of on the ground reporting, expert David Rieff offers a masterly review about whether ending extreme poverty and widespread hunger is within our reach as increasingly promised.